2020
DOI: 10.3390/d12040144
|View full text |Cite
|
Sign up to set email alerts
|

News from the Sea: A New Genus and Seven New Species in the Pleosporalean Families Roussoellaceae and Thyridariaceae

Abstract: Nineteen fungal strains associated with the seagrass Posidonia oceanica, with the green alga Flabellia petiolata, and the brown alga Padina pavonica were collected in the Mediterranean Sea. These strains were previously identified at the family level and hypothesised to be undescribed species. Strains were examined by deep multi-loci phylogenetic and morphological analyses. Maximum-likelihood and Bayesian phylogenies proved that Parathyridariella gen. nov. is a distinct genus in the family Thyriadriaceae. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Most species of Roussoella are saprobic on terrestrial plants from monocotyledons, such as bamboo, palms and other large grasses (Hyde 1997, Liu et al 2014, Ariyawansa et al 2015, Jiang et al 2019 (Poli et al 2020). Several Roussoella species have been reported from the northern part of Thailand (Liu et al 2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most species of Roussoella are saprobic on terrestrial plants from monocotyledons, such as bamboo, palms and other large grasses (Hyde 1997, Liu et al 2014, Ariyawansa et al 2015, Jiang et al 2019 (Poli et al 2020). Several Roussoella species have been reported from the northern part of Thailand (Liu et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Jaklitsch & Voglmayr (2016) synonymized Roussoellaceae under Thyridariaceae based on phylogenetic analysis of limited taxa. However, Tibpromma et al (2017) argued that Roussoellaceae and Thyridariaceae were separate families in Pleosporales, and this was conferred in later studies using more taxa coupled with morphology and DNA sequences (Hyde et al 2018a, Jiang et al 2019, Poli et al 2020. Roussoellaceae is now recognized as a well-resolved family in Pleosporales (Hongsanan et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Marine fungi are widespread in the oceans and colonize different ecological niches; they are found associated with organisms of all trophic levels and can act as saprobes, symbionts and parasites (Wang et al, 2012;Raghukumar, 2017;Poli et al, 2018). Despite the increasing effort of marine mycologists to contribute to the discovery of new species (Abdel- Wahab et al, 2017;Bovio et al, 2018;Devadatha et al, 2018;Poli et al, 2017Poli et al, , 2020, marine fungi are still an understudied group compared to other marine microorganisms (Tisthammer et al, 2016). Jones et al (2015) estimated that about 10,000 species of marine fungi are still waiting to be described.…”
Section: Fungimentioning
confidence: 99%
“…Diatoms are valuable in terms of their waste as they produce nanostructured and mesoporous biosilica shells (frustules) with a highly ordered hierarchical architecture. These unique, morphological, chemical, and mechanical properties make the biosilicate of diatoms a very attractive nanomaterial for a wide range of applications (Pletikapić et al, 2012). Diatom frustules have good mechanical properties, low density and a high surface area, hence they can be used as fillers to improve the mechanical properties of polymers (Lamastra et al, 2017).…”
Section: Bio-inspired Materialsmentioning
confidence: 99%
“…The Special Issue also includes an investigation into the diversity of marine fungi by Poli et al These authors reported the presence of new genera and species isolated from seagrass and algae of the Mediterranean Sea and highlighted how the families Roussoellaceae and Thyridariaceae, until now associated with terrestrial plants, are well represented also in the marine environment [6].…”
mentioning
confidence: 99%